EMP3, which is regulated by miR-663a, suppresses gallbladder cancer progression via interference with the MAPK/ERK pathway. (28th August 2018) - Ma, Qiang; Zhang, Yijian; Liang, Haibin; Zhang, Fei; Liu, Fatao; Chen, Shili; Hu, Yunping; Jiang, Lin; Hao, Yajuan; Li, Maolan; Liu, Yingbin
Abstract: Gallbladder cancer (GBC) is the most common malignancy of the biliary tract and its molecular pathogenesis is poorly understood. Aberrant expression of epithelial membrane protein-3 (EMP3) was reported in different kinds of cancers. Our study aimed to explore the elusive functional roles and the underlying molecular mechanisms of EMP3 with respect to GBC progression. The results showed that human GBC tissues exhibited decreased levels of EMP3 compared with non-malignant tissues. Kaplan–Meier analysis indicated that low expression of EMP3 was associated with poor prognosis of GBC patients. Upregulation of EMP3 repressed GBC cell proliferation, migration and invasion both in vitro and in vivo . Conversely, EMP3 silencing promoted GBC cell growth and metastasis. Additionally, we found that EMP3 was a target gene of miR-663a, and downregulation of EMP3 in GBC was attributed to the overexpression of miR-663a. Furthermore, miR-663a was proven to be a tumor-promoting factor mediating GBC development. Finally, we demonstrated that downregulation of EMP3 activated MAPK/ERK signaling, which modulated GBC progression. These data showed the mechanism by which EMP3 suppresses GBC progression, suggesting that the miR-663a/EMP3/MAPK/ERK axis may be a novel therapeutic target for GBC treatment. Highlights: Low EMP3 expression was associated with poor prognosis of GBC patients. EMP3 suppressed GBC cell growth and metastasis both in vitro and in vivo. EMP3 was targeted and regulated by miR-663a which was proven to be a tumor-promoting factor. EMP3 modulated GBC progression by inactivating MAPK/ERK signaling.